(untitled) (Philological Studies, 2022)
Macedonian animated films in the last century would have their most fruitful period from 1971 until 1991. During this time, its most significant achievements were attained as witnessed by the steady flow of awards and recognitions bestowed by the most relevant festivals and critics thus earning it the epithet Skopje School of Animated Film. The Project Macedonian Animated Film 1971-1991 evidence this period reviewing materials from the past analogous times: thorough archival research, detection of material for restoration and digitization for its further protection and consolidation, and its open, work in progress concept leaves room for new research and additions to the already rich digital archive.